Effect of Eucheuma cottonii extract on interleukin-1 level and caspase-3 expression in borax-induced ratâ€™s hepatocyte - Muhyi, Ahmad; Wibowo, Joko Wahyu; Priyantini, Sri (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Borax is a hepatotoxic substance and induces oxidative stress in hepatocytes. It may trigger the expression of pro-inflammatory cytokines like Interleukin-1 and apoptotic signals like Caspase-3. Extract of the seaweed Eucheuma cottonii contains carotenoids and flavonoids which suppress oxidative stress in hepatocyte. This study was conducted to determine the effect of E. cottonii extract on borax-induced Interleukin-1 and Caspase-3 expression in rat hepatocyte cells. This research employs a posttest-control group design. Twenty Wistar male rats were separated into four groups: control group (K1) received no intervention, K2 received Na-CMC 0.5% for 17 days and Borax 40 mg/200 g on the fourth day every hour for 14 days, P1 and P2groupsÂ  were administered E. cottonii extracts at doses of 600 mg/200 g and 1200 mg/200 g for 17 days, respectively, followed byborax induction at a dose of 40 mg/200 g on the fourth day with a one-hour interval for 14 days. Interleukin-1 (IL-1) levels were measured with ELISA, while caspase-3 expression was measured with PCR. For the statistical analysis, Kruskal Wallis and Mann Whitney were used. The level of IL-1 in P2 was significantly lower than in K2 (p<0.05). Caspase-3 expression was significantly lower in P1 and P2 than in K2 (p<0.05). IL-1 level and caspase-3 expression of hepatocytes are affected by administration of E. cottonii extract. The extract has the ability to prevent inflammation and hepatocyte apoptosis.<img src="data:image/png;base64,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